2003
DOI: 10.1002/cm.10127
|View full text |Cite
|
Sign up to set email alerts
|

Gliding movement in Peranema trichophorum is powered by flagellar surface motility

Abstract: A colorless euglenoid flagellate Peranema trichophorum shows unique unidirectional gliding cell locomotion on the substratum at velocities up to 30 micro m/s by an as yet unexplained mechanism. In this study, we found that (1) treatment with NiCl(2) inhibited flagellar beating without any effect on gliding movement; (2) water currents applied to a gliding cell from opposite sides caused detachment of the cell body from the substratum. With only the anterior flagellum adhering to the substratum, gliding movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
(28 reference statements)
0
44
0
Order By: Relevance
“…A major difference between euglenids and dinoflagellates, however, is the structure, orientation and motility of the anterior flagellum. The anterior paraxial rod in euglenids is oriented on the ventral side of the axoneme, is stiff and held straight in front of the cell; the paraxial rod functions with the flagellar hairs to produce gliding forces (16). By contrast, the anterior flagellum of dinoflagellates forms a transverse loop or spiral around the circumference of the cell and usually sits within a transverse groove called the cingulum (Fig.…”
Section: Cellular Organization Of Euglenids and Dinoflagellatesmentioning
confidence: 99%
“…A major difference between euglenids and dinoflagellates, however, is the structure, orientation and motility of the anterior flagellum. The anterior paraxial rod in euglenids is oriented on the ventral side of the axoneme, is stiff and held straight in front of the cell; the paraxial rod functions with the flagellar hairs to produce gliding forces (16). By contrast, the anterior flagellum of dinoflagellates forms a transverse loop or spiral around the circumference of the cell and usually sits within a transverse groove called the cingulum (Fig.…”
Section: Cellular Organization Of Euglenids and Dinoflagellatesmentioning
confidence: 99%
“…For gliding, interaction of motors with transmembrane proteins, together with a clutch mechanism to engage and disengage the motors and a system for returning motors to the tip of the axoneme, could have evolved into gliding with little modification of pre-existing systems. Flagellar-dependent gliding is only well documented as a form of motility in a few Bikont organisms such as Chlamydomonas (Bloodgood, 1981) and Peranema (Saito et al, 2003;Tamm, 1967), but ciliary surface motility has also been observed in Unikont metazoa, including sea urchin embryo cilia (Bloodgood, 1980) and mammalian primary cilia (Bowser and Leonard, 1992), and the underlying motility, intraflagellar transport, is widespread and essential for the assembly and maintenance of both motile and non-motile cilia and flagella (Pazour and Rosenbaum, 2002). Reassessment of the distribution of flagellar gliding motility, especially among the numerous soil amoeboflagellates, may show that it is more widespread than we know at present.…”
Section: The Origins Of 9+2 Organellesmentioning
confidence: 99%
“…There is no sexual cycle or photosynthesis to interfere with behavioral studies. Saito et al (32) have used Peranema as a model system for gliding motility. Furthermore, they have developed a monoxenic culture system so that it is possible to obtain sufficient bacterium-free cells for biochemical and molecular biological studies.…”
Section: Discussionmentioning
confidence: 99%
“…This choice of terminology follows the advice of Irene Manton [24] and Tom Cavalier-Smith [5], who says "the word flagellum should be dropped altogether from eukaryotic biology.") These fully grown or mature cells are pulled forward along a surface by the cell surface motility of the proximal five-sixths of the anterior cilium (32). The cilium is straight except for the waving anterior one-sixth, which presumably senses particles of food and obstacles.…”
mentioning
confidence: 99%